Transparent laser ceramics by stereolithography. (October 2020) - Hostaša, Jan; Schwentenwein, Martin; Toci, Guido; Esposito, Laura; Brouczek, Dominik; Piancastelli, Andreana; Pirri, Angela; Patrizi, Barbara; Vannini, Matteo; Biasini, Valentina
Abstract: A lithography-based additive manufacturing technique was used for the first time to produce laser-emitting transparent 10 at.% Yb-doped yttrium aluminum garnet (Yb:YAG) ceramics from a mixture of oxide powders as starting materials. The ceramics were densified by vacuum sintering. Output power of more than 2.16 W and a slope efficiency of 17.6% were achieved under quasi-continuous-wave laser pumping. Graphical abstract: Image, graphical abstract